Training of Traditional Birth Attendants on Prevention of Mother to Child Transmission of HIV: Effect on Their Knowledge and Delivery of Prevention of Mother to Child Transmission of HIV Services in Igbagu, Ebonyi State Nigeria - , A. F. Una; , L. U. Ogbonnaya; , C. N. Obionu; , K. N. Omeje; , E. I. Obi (Archives of Current Research International, 2017)
Aims: To assess the traditional birth attendants’ (TBAs’) knowledge of HIV and prevention of mother to child transmission (PMTCT) of HIV and their practice of PMTCT of HIV services delivery. It was also designed to train them on PMTCT of HIV and mobilization of the pregnant women in the community to access PMTCT of HIV services in a formal health facility. Study Design: The study was a cross-sectional descriptive study with an interventional component Place and Duration of Study: The 8 months study was conducted in Igbagu Community in Izzi Local Government Area of Ebonyi State Nigeria, in 2015. Methodology: A total population study of all TBAs in the study area identified using the snowball non-probabability sampling method was conducted. Baseline assessment of their knowledge and practice of PMTCT of HIV services delivery was done. They were subsequently trained on PMTCT of HIV and on mobilization and referral of pregnant women to access HIV counselling and testing (HCT) and other PMTCT of HIV services at a designated health facility in the community. At the end of the study, post training PMTCT of HIV knowledge assessment and determination of the number of pregnant women who complied with the TBAs’ referral for PMTCT of HIV serices at the health facility were carried out. Results: Assessment of the TBAs’ composite knowledge of modes of HIV transmission and preventive measures gave the mean score of 14.8% ± 11.5% and 68.8% ± 12.5% pre and post training respectively. The difference was statistically significant (Z = - 5.2; p < 0.001). Following the training, all the TBAs were referring their clients to health facility for PMTCT of HIV services compared to 10 (28.6%), before the study. Fifty two pregnant women complied with referral by the TBAs to the health facility for PMTCT of HIV services out of the 129 pregnant mothers who visited them during the study, giving a compliance rate of 40.3%.